Facial soft tissue thickness in North Indian adult population - Tanushri Saxena; Sunil Ramchandra Panat; N C Sangamesh; Anand Choudhary; Ashish Aggarwal; Nidhi Yadav (Wolters Kluwer Medknow Publications, 2012)
Objectives: Forensic facial reconstruction is an attempt to reproduce a likeness of facial features of an individual, based on characteristics of the skull, for the purpose of individual identification - The aim of this study was to determine the soft tissue thickness values of individuals of Bareilly population, Uttar Pradesh, India and to evaluate whether these values can help in forensic identification. Study design: A total of 40 individuals (19 males, 21 females) were evaluated using spiral computed tomographic (CT) scan with 2 mm slice thickness in axial sections and soft tissue thicknesses were measured at seven midfacial anthropological facial landmarks. Results: It was found that facial soft tissue thickness values decreased with age. Soft tissue thickness values were less in females than in males, except at ramus region. Comparing the left and right values in individuals it was found to be not significant. Conclusion: Soft tissue thickness values are an important factor in facial reconstruction and also help in forensic identification of an individual. CT scan gives a good representation of these values and hence is considered an important tool in facial reconstruction- This study has been conducted in North Indian population and further studies with larger sample size can surely add to the data regarding soft tissue thicknesses.